Ecological mechanism of climate‐mediated selection in a rapidly evolving invasive species. (7th February 2021) - Mushegian, Alexandra A.; Neupane, Naresh; Batz, Zachary; Mogi, Motoyoshi; Tuno, Nobuko; Toma, Takako; Miyagi, Ichiro; Ries, Leslie; Armbruster, Peter A.
Abstract: Recurring seasonal changes can lead to the evolution of phenological cues. For example, many arthropods undergo photoperiodic diapause, a programmed developmental arrest induced by short autumnal day length. The selective mechanisms that determine the timing of autumnal diapause initiation have not been empirically identified. We quantified latitudinal clines in genetically determined diapause timing of an invasive mosquito, Aedes albopictus, on two continents. We show that variation in diapause timing within and between continents is explained by a novel application of a growing degree day (GDD) model that delineates a location‐specific deadline after which it is not possible to complete an additional full life cycle. GDD models are widely used to predict spring phenology by modelling growth and development as physiological responses to ambient temperatures. Our results show that the energy accumulation dynamics represented by GDD models have also led to the evolution of an anticipatory life‐history cue in autumn. Abstract : We show that variation in the timing of a mosquito's autumnal diapause timing within and between continents is explained by a growing degree day (GDD) model that delineates a location‐specific deadline after which it is not possible to complete an additional full life cycle. GDD models are widely used to predict spring phenology by modeling growth and development as physiological responses to ambient temperatures. Our results show that the energy accumulation dynamics represented by GDD models have also led to the evolution of an anticipatory life‐history cue in autumn.